Core Disaster Medicine Education (CDME) for Emergency Medicine Residents in the United States. Issue 5 (28th August 2019) - Sarin, Ritu R.; Biddinger, Paul; Brown, John; Burstein, Jonathan L.; Burkle, Frederick M.; Char, Douglas; Ciottone, Gregory; Hick, John L.; Koenig, Kristi L.; Little, Charles; Schultz, Carl; Maggin, Jeremy; et al.
Abstract: Objectives: Disaster Medicine (DM) education for Emergency Medicine (EM) residents is highly variable due to time constraints, competing priorities, and program expertise. The investigators' aim was to define and prioritize DM core competencies for EM residency programs through consensus opinion of experts and EM professional organization representatives. Methods: Investigators utilized a modified Delphi methodology to generate a recommended, prioritized core curriculum of 40 DM educational topics for EM residencies. Results: The DM topics recommended and outlined for inclusion in EM residency training included: patient triage in disasters, surge capacity, introduction to disaster nomenclature, blast injuries, hospital disaster mitigation, preparedness, planning and response, hospital response to chemical mass-casualty incident (MCI), decontamination indications and issues, trauma MCI, disaster exercises and training, biological agents, personal protective equipment, and hospital response to radiation MCI. Conclusions: This expert-consensus-driven, prioritized ranking of DM topics may serve as the core curriculum for US EM residency programs.